2016
DOI: 10.1021/acs.energyfuels.5b02561
|View full text |Cite
|
Sign up to set email alerts
|

Soot Concentrations in an Atmospheric Entrained Flow Gasifier with Variations in Fuel and Burner Configuration Studied Using Diode-Laser Extinction Measurements

Abstract: Soot concentration measurements were performed using diode-laser extinction in an atmospheric air-blown entrained flow gasifier at two vertical levels. The gasifier was operated at different air-fuel equivalence ratios and with variations in fuel and burner configurations. Two fuels were investigated: wood powder and peat powder. These were burned using two burner configurations, one giving a rotating flow inside the gasifier (swirl), and one where the fuel and air were injected parallel with the gasifier axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Simonsson et al [39] reported an atmospheric entrained flow gasifier experiment with stem wood and peat as fuels. A similar but somewhat simplified simulation setup is configured as seen in Fig.…”
Section: Figmentioning
confidence: 99%
“…Simonsson et al [39] reported an atmospheric entrained flow gasifier experiment with stem wood and peat as fuels. A similar but somewhat simplified simulation setup is configured as seen in Fig.…”
Section: Figmentioning
confidence: 99%
“…In the case of Peat, higher wavelengths give higher soot concentrations, whereas the behavior is opposite for Wood. Previous studies on Wood [17] revealed that the soot aerodynamic diameter increases gradually with decreasing lambda and is at least a factor of 2 larger than for Peat. This suggests that, for Wood, the Rayleigh criterion is violated at 639 nm and that the contribution of scattering to the reduction in transmittance of Sensor 3 can explain the difference to Sensors 1 and 2.…”
Section: Soot and Carbon Conversionmentioning
confidence: 83%
“…1) operated at 0.1 MWth [17]. The gasifier has the shape of a standing cylinder with flat top and conical bottom.…”
Section: Reactor Facilitymentioning
confidence: 99%
“…The extinction measurement system was an extended version of a previous system developed for in-situ flame measurements (Simonsson et al 2015), as well as practical combustion and gasification devices (Simonsson et al 2016). In the present setup a four-wavelength version was used.…”
Section: Diagnostic Methodsmentioning
confidence: 99%